Analysis of unconfined compressive and shear strength of clay mixed with a based combination of rice husk ash and NaOH - Ance Fungki Manik; Nahesson Panjaitan; Suhairiani Suhairiani; Febryani Gabriella (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2025)
Clay is a type of soil that is generally characterized by its low load-bearing capacity. Due to the nature of clay minerals, which easily absorb and store water, clay soil is not generally considered suitable for use as a basic building material. This study analyzes changes in the unconfined compressive strength and shear strength of clay soil mixed with rice husk ash (RHA), NaOH, and a combination of rice husk ash and NaOH. The research method involves laboratory tests on original soil samples and soil samples that have been stabilized with varying levels of additives. The results showed that adding rice husk ash, NaOH, or both changed the properties in all tested samples. Unconfined compressive strength testing with varying amounts of rice husk ash (8%, 17%, 25%) showed the highest compressive strength increase of 28.19% at 8% RHA. Meanwhile, adding different amounts of solid NaOH (10%, 14%, and 25%) did not increase the soil's unconfined compressive strength. Mixing rice husk ash and NaOH also did not increase the soil's unconfined compressive strength; rather, it decreased the original soil's rigidity. Direct shear strength tests with RHA variations (8%, 17%, and 25%) showed the greatest increase at 8% of the original soil content, reaching 28.9%. This value decreased with an increased RHA percentage. Adding solid NaOH at different ratios (10%, 14%, and 25%) showed the greatest increase at 10%, with an increase of 14.68%; however, it decreased with increasing NaOH content. The mixture of RHA and NaOH increased in all variations. The highest direct shear strength value occurred in the 25% RHA + 25% NaOH mixture, which increased by 54.13% compared to the original soil. This study showed that RHA can increase soil strength through reactions with water and soil particles. However, these results emphasize the importance of selecting the appropriate types and ratios of stabilizer materials in accordance with engineering requirements.